Obtaining Ionites from Cotton Grinding Waste (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
This in the article cotton combing from enterprises came out waste ion exchanger materials – ionites convert opportunity studied. Research to the results according to waste special chemical processing to give through effective ionites to take possible. Obtained ion exchangeability of ionites features from the test held, their water cleaning in the processes application opportunity evaluated. This method ecological problems reduce and industry from waste effective of use promising from directions one as seeing is released.